Humans Prefer Curved Visual Objects - Bar, Moshe; Neta, Maital (Psychological Science, 2006)
People constantly make snap judgments about objects encountered in the environment. Such rapid judgments must be based on the physical properties of the targets, but the nature of these properties is yet unknown. We hypothesized that sharp transitions in contour might convey a sense of threat, and therefore trigger a negative bias. Our results were consistent with this hypothesis. The type of contour a visual object possesses—whether the contour is sharp angled or curved—has a critical influence on people's attitude toward that object.